An Unusual Benign Vascular Ovarian Tumor - Rutigliani, Mariangela; Davide.Lijoi,; DeCensi, Andrea; Paleari, Laura (Archives of Clinical and Medical Case Reports, 2021)
Ovarian hemangiomas are very rare benign tumors of the female genital tract. Most cases are small lesions that are discovered by chance. Although they are often an incidental finding at surgery, these lesions may sporadically be associated with systemic manifestations. Here, we describe a 63 year-old woman with a right ovary benign hemangioma who presented with a clinically suspicious left ovarian torsion.